Impact of DDD and VVIR Stimulation Modes on Functional Capacity and Quality of Life of Chagasic Patients - Santana, Débora Rodrigues; Santana Filho, Geraldo Paulino; Rocha, Zander Bastos; Lima, Antonio Malan Cavalcanti; Nery, Max Weyler; Rassi, Salvador; Gardenghi, Giulliano (JOURNAL OF CARDIAC ARRHYTHMIAS, 2019)
Introduction: Atrioventricular stimulation provides hemodynamic benefits over the isolated ventricular rate, but this advantage is not completely established in chagasic patients with systolic dysfunction. Objectives: To evaluate the influence of DDD and VVIR stimulation modes on functional capacity, quality of life (QoL) and laboratory abnormalities of a natriuretic peptide in chagasic patients with ventricular dysfunction submitted to pacemaker implantation. Methods: Twenty patients (55% male) with a mean age of 62.7 (± 9.9 years) and a mean ejection fraction of 41.8% (± 2.8) were prospectively studied. Alternately, patients received pacing in the DDD and VVIR modes for a period of three months under each schedule. The minimum percentage of ventricular pacing was 80%. After each period, the patient was submitted to the six-minute walk test (6MWT), QOL assessment by the Minnesota Living with Heart Failure Questionnaire (MLHFQ) and the Assay of QUAlity of life and RELated events (AQUAREL). Laboratory evaluation was performed with the N-terminal fraction of the brain natriuretic peptide (N-terminal pro b-type natriuretic peptide - NT-proBNP). Results: The mean distance walked on the 6MWT in the DDD and VVIR modes were 390.60 (± 52.71) and 396.30 (± 52.71) meters respectively (p = 0.160). Results of lower QOL were found, considering the physical domain of the MLHFQ (p = 0.03) and the domains of effort dyspnea (p = 0.05) and arrhythmia (p <0.001) of the AQUAREL with the VVIR mode. NT-proBNP levels increased significantly with stimulation in VVIR mode (p < 0.001). Conclusion: After three months of stimulation with the VVIR mode, there was worsening of the QoL of the chagasic patients and increase of the levels of NT-proBNP (clinical trial record: ReBEc RBR-53x476).